Computer-aided discovery of aminopyridines as novel JAK2 inhibitors. Issue 5 (1st March 2015) - Zhao, Chao; Yang, Su Hui; Khadka, Daulat Bikram; Jin, Yifeng; Lee, Kyung-Tae; Cho, Won-Jea
Graphical abstract: Abstract: The Janus kinase 2 (JAK2)-mediated signaling pathway plays an important role in controlling cell survival, proliferation, and differentiation. In recent years, genetic, biological, and physiological evidence has established JAK2 inhibitors as effective chemotherapeutic agents for the treatment of many different cancers. For this reason, we sought to identify novel small molecule inhibitors of JAK2. Using Surflex-Dock software, we tested 3010 compounds with known chemical structures in silico for their ability to interact with the JAK2 ATP-binding pocket. We selected the 10 highest-scoring compounds and tested their abilities to inhibit JAK2 activity in vitro. Compound1a (ethyl 1-(5-((3-methoxyphenyl)carbamoyl)-3-nitropyridin-2-yl)piperidine-4-carboxylate) was identified. Optimization of1a using docking studies led to the discovery of compounds1b and1d, potent JAK2 inhibitors. Furthermore, as V-shaped kinase inhibitors can curve around the protein backbone and access deep into the pocket, we developed a new series of compounds with a non-linear sulfonamide bond. Nine compounds were prepared and evaluated for JAK2 inhibitory effects. Compounds7e (IC50  = 6.9 μM) and7h (IC50  = 12.2 μM) showed better JAK2 inhibition, validating our design approach. This study successfully applied virtual screening for hit discovery, and a docking study for hit optimization. In addition, a novel approach to drug discovery, combining structure- and shape-based drug design, facilitated the design of more potent JAK2 inhibitors. The methods provide a guide for future development of inhibitors targeting JAK2 and other kinases.